2019
DOI: 10.1016/j.renene.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Series of detail comparison and optimization of thermoelectric element geometry considering the PV effect

Abstract: This study investigates the optimum geometry for maximum efficiency of a hybrid PV-TE uni-couple using Finite Element Method. COMSOL Multiphysics is used to solve the 3-Dimensional heat transfer equations considering thermoelectric materials with temperature dependent properties. Two types of thermoelectric element geometry area ratios are considered for the range 0.5 ≤ ܴ ≤ 2 and 0.5 ≤ ܴ ௌ ≤ 2 . Nine different geometric configurations are analysed for two different PV cells. Effects of thermoelectric generator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 44 publications
1
34
0
Order By: Relevance
“…The task of improving the performance of a TEG is often related to the optimizing its leg geometry. By leg geometry, it implies the thermoelement area ratio ()AnAp of the n‐ and p‐type legs or the area ratio of the hot and cold junction ()AhAc. Geometric optimization of TEG involves finding the number of thermocouple and height of leg that result in maximum electrical output. Various research works have been conducted to improve the performance of TEG by changing the TE leg geometry.…”
Section: Hybrid Pv‐tegmentioning
confidence: 99%
See 3 more Smart Citations
“…The task of improving the performance of a TEG is often related to the optimizing its leg geometry. By leg geometry, it implies the thermoelement area ratio ()AnAp of the n‐ and p‐type legs or the area ratio of the hot and cold junction ()AhAc. Geometric optimization of TEG involves finding the number of thermocouple and height of leg that result in maximum electrical output. Various research works have been conducted to improve the performance of TEG by changing the TE leg geometry.…”
Section: Hybrid Pv‐tegmentioning
confidence: 99%
“…They concluded that a higher total efficiency could be achieved by employing a large cross‐sectional area and lower TEG height under constant concentration ratio and cold side temperature. Recently, Shittu et al carried out a detailed comparison and geometric optimization of thermoelement in PV‐TEG system while considering the temperature coefficient for two different solar cells. Their results indicated a better performance for a symmetrical leg geometry for a PV with efficiency temperature coefficient of 4 × 10 −3 K −1 .…”
Section: Hybrid Pv‐tegmentioning
confidence: 99%
See 2 more Smart Citations
“…26,27 Theoretical analysis of trapezoidal leg geometries indicates that these geometries can lead to higher device efficiency. [28][29][30]…”
Section: A Thermal Resistance Considerationsmentioning
confidence: 99%